Sharia Value-Based Learning Environment and Students’ Career Choice (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
The purpose of this study is to find out whether the sharia value-based learning environment influences the career choice of sharia economics students at Islamic Financial Industries (IFIs). Learning is one of the crucial factors that could shape career choices referring to Social Cognitive Career Theory (SCCT). A quantitative approach is employed. Questionnaires totaling 378 were filled by students from three (3) types of universities in East Java, Indonesia. Path analysis and different tests using Partial Least Square (PLS) 3.0 and SPSS ver. Twenty-three were conducted. The weight of courses, learning, and lecturers' motivation positively affected career intention at IFIs. Students from the public–non-Islamic universities perceived the highest learning and motivation, and the lowest was public–Islamic universities. It might be because the Islamic culture at public-Islamic universities might form an ideal perspective for the contemporary IFIs. Besides, students who completed an internship at IFIs had the highest intention; meanwhile, students who have interned at non-IFIs showed the lowest career intention at IFIs. The implications of this study are learning environment should more involve sharia values. Besides, students should intern at IFIs to choose a career at IFIs to contribute to developing sharia economics.